Helmut Lachenmann und seine Zeit - Hiekel, Jörn Peter (Lilienthal Laaber, 2023)
Helmut Lachenmann has long been one of the defining figures of contemporary music. His works are performed worldwide and their status is beyond question. The monograph 'Helmut Lachenmann und seine Zeit' shows, on the basis of detailed studies of sources and works, that the composer's path is consistent while at the same time the conceptions of his works that have emerged over the course of more than 60 years are borne by significant distinctions, new approaches and openness to change. Lachenmann's oeuvre, although it can be regarded with good reason as highly original, has many resonances and reflections of other compositional approaches as well as of various philosophical positions. And it conveys in an equally elementary and exemplary way what the idea of an existential experience of art can mean within the broad spectrum of today's overall culture.
Mit 19 Notenbeispielen und 24 Abbildungen
Keywords: Lachenmann, Helmut -- 1935-; Composer; Biography